2011
DOI: 10.1136/heartjnl-2011-300727
|View full text |Cite
|
Sign up to set email alerts
|

Heart valve prosthesis selection in patients with end-stage renal disease requiring dialysis: a systematic review and meta-analysis

Abstract: A meta-analysis of the published literature demonstrates no survival difference following valve replacement with either bioprostheses or mechanical prosthesis in patients with ESRD on dialysis. Bioprosthetic valve replacement was associated with fewer valve-related complications. Although this meta-analysis cannot discriminate between the sites of valve implant, these data can likely be extended to include at least aortic valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 20 publications
2
27
1
1
Order By: Relevance
“…In addition to the above findings, a meta-analysis of the published literature demonstrates no survival difference following valve replacement with either bioprosthesis or mechanical prosthesis in patients with ESRD on dialysis. Some recent studies reported that early structural valve deterioration was uncommon, even in dialysis patients, but others showed that it occurred even in new-generation bioprosthetic valves [21,22]. In fact, these reports also support our current study, which have similar outcomes than the present paper.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the above findings, a meta-analysis of the published literature demonstrates no survival difference following valve replacement with either bioprosthesis or mechanical prosthesis in patients with ESRD on dialysis. Some recent studies reported that early structural valve deterioration was uncommon, even in dialysis patients, but others showed that it occurred even in new-generation bioprosthetic valves [21,22]. In fact, these reports also support our current study, which have similar outcomes than the present paper.…”
Section: Discussionsupporting
confidence: 91%
“…A number of recent studies have demonstrated equivalent survival rates between bioprosthetic and mechanical valves dialysis patients (20). Our meta-analysis also confirms with previous studies by demonstrating the same equivalence of mortality and survival rates among valve prosthesis choice (31).…”
Section: Discussionsupporting
confidence: 89%
“…26 A recent meta-analysis combined nine studies comparing mechanical and bioprosthetic valves in the ESRD population and found no survival difference but fewer valve-related complications with bioprostheses. 27 …”
Section: Discussionmentioning
confidence: 99%